Deixis Analysis in the Novel “Kala” Works of Syahid Muhammad and Stefani Bella: Pragmatic Study - Sarmila Suhita Devi Damanik; Yusni Khairul Amri (LingLit Journal Scientific Journal for Linguistics and Literature, 2023)
Deixis is the study of speech acts produced by speakers either directly or in writing. Language as a communication tool is a form of communication in the form of words or expressions that function as pointers or deixis. This study aims to describe the use of deixis in the novel Kala by Syahid Muhammad and Stefani Bella. This study used a qualitative descriptive method. The data of this research is the content of the text of the novel Kala which contains deixis. The source of the research data is the novel Kala which is divided into five types, namely (1) persona deixis, (2) place deixis, (3) time deixis, (4) discourse deixis, and (5) social deixis. Data collection techniques using document studies. The data analysis technique uses five steps, namely re-reading carefully, collecting data from the contents of the novel, underlining the contents of the story related to deixis elements, describing the findings of researchers in the novel and concluding the results of the research. The results of the analysis of the research data found that there were 8,550 deixis, namely 2,593 persona deixis which were divided into 324 first persona deixis, 430 second persona deixis, 230 third persona deixis, 89 first singular persona deixis, 76 first persona deixis fruit, second person singular deixis 267, second person plural deixis 121, third person singular deixis 143, third person plural deixis 92. There are 682 place deixis. There are 555 time deixis, 16 discourse deixis, and 240 social deixis.